Dual Effects of Cyclooxygenase Inhibitors in Combination With CD19.CAR-T Cell Immunotherapy - Yang, Mingya; Wang, Lei; Ni, Ming; Neuber, Brigitte; Wang, Sanmei; Gong, Wenjie; Sauer, Tim; Schubert, Maria-Luisa; Hückelhoven-Krauss, Angela; Xia, Ruixiang; Ge, Jian; Kleist, Christian; et al. (Frontiers in Immunology, 2021)
CAR-T cells targeting CD19 came into clinical practice for the treatment of B cell lymphoma in 2018. However, patients being treated for B cell lymphoma often suffer from comorbidities such as chronic pain, cardiovascular diseases and arthritis. Thus, these patients frequently receive concomitant medications that include NSAIDs like COX inhibitors. Celecoxib, a selective COX-2 inhibitor, and aspirin, a non-selective COX-1 and COX-2 inhibitor, are being used as anti-inflammatory, analgesic and anti-pyretic drugs. In addition, several studies have also focused on the anti-neoplastic properties of COX-inhibitors. As the influence of COX-inhibitors on CD19.CAR-T cells is still unknown, we investigated the effect of celecoxib and aspirin on the quantity and quality of CD19.CAR-T cells at different concentrations with special regard to cytotoxicity, activation, cytokine release, proliferation and exhaustion. A significant effect on CAR-T cells could be observed for 0.1 mmol/L of celecoxib and for 4 mmol/L of aspirin. At these concentrations, we found that both COX-inhibitors could induce intrinsic apoptosis of CD19.CAR-T cells showing a significant reduction in the ratio of JC-10red to JC-10green CAR-T cells from 6.46 ± 7.03 to 1.76 ± 0.67 by celecoxib and to 4.41 ± 0.32 by aspirin, respectively. Additionally, the ratios of JC-10red to JC-10green Daudi cells were also decreased from 3.41 ± 0.30 to 0.77 ± 0.06 by celecoxib and to 1.26 ± 0.04 by aspirin, respectively. Although the cytokine release by CD19.CAR-T cells upon activation was not hampered by both COX-inhibitors, activation and proliferation of CAR-T cells were significantly inhibited via diminishing the NF-ĸB signaling pathway by a significant down-regulation (about 45%) of expression of CD27 on CD4+/CD8+ CAR-T cells, followed by a clear decrease of phosphorylated NF-ĸB p65 in both CD4+/CD8+ CAR-T cells by a factor of 1.8. Of note, COX-inhibitors hampered expansion and induced exhaustion of CAR-T cells in an antigen stress assay. Collectively, our findings indicate that the use of COX-inhibitors is a double-edged sword that not only induces apoptosis in tumor cells but also impairs the quantity and quality of CAR-T cells. Therefore, COX-inhibitors should be used with caution in patients with B cell lymphoma under CAR-T cell therapy.